The Relationship Between Customer Relationship Management and Customer Loyalty and the Moderation of Customer Trust - Ade Setiawan; Lia Yuldinawati; Maria Apsari Sugiat (Journal of Social Research, 2025)
Customer trust and loyalty are things that help businesses grow. Factors that influence customer trust and loyalty are evidenced by customer satisfaction with the services provided by the company. Companies observe Customer Relationship Management (CRM) not only to increase company revenue, but also believe that Customer Relationship Management (CRM) should be at the heart of all business strategies. Customer Relationship Management (CRM) is used by companies to understand customers and aspects that affect customer satisfaction and loyalty. This study aims to determine how much influence the moderating role, namely customer trust with the customer relationship management (CRM) component and its relationship with customer loyalty at PLN UP3 Kupang. This research applies quantitative methods with a causal approach. A total of 300 respondents who are potential customers or the B2B segment of PLN UP3 Kupang were sampled. The data obtained were analyzed using the Structural Equation Modeling (SEM) method to evaluate the relationship between variables and test the mediation and moderation effects in the conceptual model developed. The results showed that of the five components of Customer Relationship Management which include customer knowledge, customer orientation, customer advocacy, customer engagement, and technological capability, only three variables were proven to have a positive and significant influence on customer loyalty. The three variables are customer knowledge, customer advocacy, and customer trust.